Quantification of Bedding Rock Slope Deformation Rate Using Guided Wave Monitoring - Zheng, Changsong; He, Wen; Huang, Chongjie; Chen, Hao; Xiao, Changbo (Frontiers in Earth Science, 2022)
The guided wave technique is applied to slope stability monitoring to overcome the high attenuation characteristics of acoustic emission propagation in rock and soil materials. The shear tests of "guided wave meter" (GWM) with different deformation rates were carried out, and the effects of the material and particle size of the coupling medium and the diameter of the waveguide rod on the flexural guided wave ring down count were studied, and the relationship between the deformation rate of the slope and the flexural guided wave parameters was analyzed. The results show that the flexural guided wave ring down count rate increases with the increase of deformation in the loading process. The GWM filled with quartz sand particles produces more flexural guided wave ring down counts than those filled with gravel particles. From the twelve groups of GWM shear tests, it can be seen that the GWM with the combination of 16 mm waveguide rod and 4~8 mm quartz sand produces the highest cumulative flexural guided wave ring down counts. The combination is used as an optimized GWM. By applying different deformation rates to the optimized GWM, it was found that the flexural guided wave ring down count rate at different deformation rates tended to increase and was distributed in a fan shape. The cumulative flexural guided wave ring down count has an excellent linear correlation with the deformation. The slope of the cumulative ring down count curves and the deformation curves are obtained separately, which shows that the deformation rate has an excellent linear relationship with the slope of the cumulative ring down count curve, and the slope of the cumulative ring down count curve increases with the increase of the deformation rate. It provides theoretical guidance for quantifying the slope deformation rate using the flexural guided waves.